Предмет: Алгебра, автор: ОлесяЗерина

Представьте выражения в виде дроби и упростите:

1. ( a^{2} - b^2)* (frac{a^2}{a-b} -b)

2.( x^{2} -y^2) :( frac{x^2}{x+y} +y)

Ответы

Автор ответа: Artem112
0
( a^{2} - b^2) (frac{a^2}{a-b} -b)=
( a^{2} - b^2) (frac{a^2-ab+b^2}{a-b} )=
\
=frac{(a-b)(a+b)(a^2-ab+b^2)}{a-b} =
(a+b)(a^2-ab+b^2)=a^3+b^3

( x^{2} -y^2) :( frac{x^2}{x+y} +y)=
( x^{2} -y^2) :( frac{x^2+xy+y^2}{x+y} )=
 frac{(x+y)(x-y)(x+y)}{x^2+xy+y^2}
Похожие вопросы
Предмет: Алгебра, автор: valparshonak